Assessing Factors Affecting Building Information Model Usage Among Professionals in the Construction Industry - Ogunbayo, Babatunde Fatai; Aigbavboa, Clinton (International Journal of Sustainable Construction Engineering and Technology, 2024)
BIM is a cooperative approach utilising a computer-generated model to coordinate and manage information throughout the project life cycle. However, BIM usage among construction professionals is affected by different factors toward reducing wastage in the construction processes and operations. This study evaluates the factors influencing BIM adoption among construction industry professionals. To gather data, structured questionnaires were administered to a sample of 70 construction professionals in Gauteng province, South Africa, using systematic random sampling techniques, with a focus on identifying key factors impacting BIM utilisation in the industry. The questionnaire data were analysed using descriptive statistical methods. A statistical equation was employed to calculate the study’s valid mean item score. The result of the study showed that lack of investment in BIM tools, lack of personnel training, high cost, and lack of basic BIM knowledge were the highest-ranked factors affecting BIM usage among professionals in the construction industry. In conclusion, the study established that professional bodies within the construction industry should train their members on the importance of using BIM tools for their construction processes and operations. It also indicated that the government should increase awareness of the use of BIM among construction professionals through ministries, departments, and agencies (MDAs).